A giant, well‐differentiated papillary mesothelioma of the left atrioventricular groove: Case report and brief review of the literature. Issue 9 (10th May 2019) - Wang, Xin; Ren, Weidong; Xiao, Yangjie; Qiao, Wei; Li, Ying; Cui, Li; Zhang, Xintong
Abstract: Of the primary cardiac tumors, well‐differentiated papillary mesothelioma (WDPM) is very rare, with only one case report documenting WDPM of the pericardium. We report herein a 17‐year‐old boy who had an abnormal chest X‐ray on a routine college‐entrance examination. A giant cardiac tumor was detected by echocardiography. The neoplasm was partially resected, and histopathological examination revealed a WDPM. The patient recovered without any complication.